2019
DOI: 10.1093/aje/kwz221
|View full text |Cite
|
Sign up to set email alerts
|

State School Policies as Predictors of Physical and Mental Health: A Natural Experiment in the REGARDS Cohort

Abstract: We used differences in state school policies as natural experiments to evaluate the joint influence of educational quantity and quality on late-life physical and mental health. Using US Census microsample data, historical measures of state compulsory schooling and school quality (term length, student-teacher ratio, and attendance rates) were combined via regression modeling on a scale corresponding to years of education (policy-predicted years of education (PPYEd)). PPYEd values were linked to individual-level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Using a representative sample of older Puerto Rican older adults, we found that childhood quality of education was positively related to both years of education and to baseline cognitive functioning in late life. The results generally fit with past research on the relationship between quality of education and adult health and cognition from samples based elsewhere ( Brenowitz et al, 2020 ; Crowe et al, 2013 ; Garcy & Berliner, 2018 ; Sisco et al, 2015 ). Past studies have similarly found that indicators of quality of education are more strongly associated with cross-sectional cognitive performance than change in cognition over time ( Carvalho et al, 2015 ; Crowe et al, 2013 ; Sisco et al, 2015 ).…”
Section: Discussionsupporting
confidence: 85%
“…Using a representative sample of older Puerto Rican older adults, we found that childhood quality of education was positively related to both years of education and to baseline cognitive functioning in late life. The results generally fit with past research on the relationship between quality of education and adult health and cognition from samples based elsewhere ( Brenowitz et al, 2020 ; Crowe et al, 2013 ; Garcy & Berliner, 2018 ; Sisco et al, 2015 ). Past studies have similarly found that indicators of quality of education are more strongly associated with cross-sectional cognitive performance than change in cognition over time ( Carvalho et al, 2015 ; Crowe et al, 2013 ; Sisco et al, 2015 ).…”
Section: Discussionsupporting
confidence: 85%
“…We assessed 3 state-level administrative indicators of school quality included in a previously compiled data set: school term length (ie, days in the academic year), student-teacher ratio (ie, ratio of students to instructional staff), and attendance rates (ie, fraction of enrolled children who attended on an average day). The data had been extracted from state and federal education reports, usually available biennially .…”
Section: Methodsmentioning
confidence: 99%
“…25 These indicators were selected because they were most consistently reported across states during most of the 20th century. 25 Consistent with prior research, we used birth year (from KPNC medical records) and self-reported birth state (from the MHCs) to link individuals to school quality measures at enrollment age when participants were aged 6 years. 18,26 State of birth has been shown to be a good proxy for state of school attendance in similar birth cohorts, as young children rarely move out of state between birth and school-starting age.…”
Section: Educational Qualitymentioning
confidence: 99%
“…29 When studying how education might affect ADRD risk across racial lines, it is important to examine educational quality rather than rely solely on years of education, and how it varies by region and racial group. 30,31 African Americans who were educated in the South, even if they migrated to the North later, generally had less time in school. 31 Just looking at years of education is inaccurate because a school year in the South and North were not equivalent; school years in the South were shorter with less class time and this lesser educational duration was associated with later cognitive differences.…”
Section: Research Presented At Thementioning
confidence: 99%
“…Data from the Kaiser Permanente Northern California (KPNC) Health System cohort indicates increased risk of dementia for people born in states with an increased stroke risk compared to those born outside of these states, and this increased risk was greater for African Americans than non‐Hispanic whites 29 . When studying how education might affect ADRD risk across racial lines, it is important to examine educational quality rather than rely solely on years of education, and how it varies by region and racial group 30,31 . African Americans who were educated in the South, even if they migrated to the North later, generally had less time in school 31 .…”
Section: Current Information On Potential Disparities and Racial Diffmentioning
confidence: 99%